Tools to Measure Oxygen Concentration and Oxygen Flow Rate in Continuous Positive Airway Pressure - Ade Putra; Tri Bowo Indrato; Liliek Soetjiatie (Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2019)
Measuring oxygen concentration and measuring the flow of oxygen is a tool used to measure the percentage of oxygen content and oxygen flow rate in CPAP. This tool uses the OCS-03F sensor, with Arduino NANO processors then displayed on the 2X16 character LCD. Measuring the percentage of oxygen content and oxygen flow rate is carried out on CPAP for 5 measurements. The research and manufacture of this module uses the Pre-experimental method with the After Only Design design, which examines the "Oxygen Analyzer", which results in measurements compared to the traced tools to obtain high accuracy values. Based on the results of measurements on the CPAP tool at Dr. Soetomo Surabaya Hospital with oxygen level settings of 21%, 30%, 40%, 50% 60%, 70%, 80%, 90%, 100% while setting the oxygen measurement rate 1L/m, 2L /m, 3L/m, 4L/m, 5L/m, 6L/m, 7L//m, 8L/m, 9L/m 10L/m. Each measurement was carried out 5 times. For the measurement of oxygen levels the biggest error value is 5% and the smallest -0,06% while for the measurement of oxygen flow rate the biggest error value is 4% and the smallest is 0%. Based on the results of the analysis of the manufacture of oxygen levels and oxygen flow rates, it can be concluded that the manufacture of oxygen concentration measuring instruments and oxygen flow rate can work well.